Modern approaches to deploying the infrastructure of mobile intelligent systems - Kosarevskyi, Bohdan; Tetskyi, Artem (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
Subject matter: The infrastructure of mobile intelligent systems (MIS) for monitoring critical assets using groups of unmanned aerial vehicles (UAVs), integrating edge and cloud computing, load balancing methods, and cybersecurity mechanisms. Goal: To investigate the efficiency of automated resource management in MIS through adaptive scaling, heuristic optimization, and failure prediction methods to enhance system reliability and performance. Tasks To design an MIS architecture with hybrid distribution of computations between edge and cloud components; to evaluate the impact of resource balancing mechanisms under variable load conditions; to assess the effectiveness of multi-channel communication technologies in the event of primary link failure; and to implement cybersecurity methods to ensure uninterrupted system operation. Methods: Theoretical analysis of existing approaches, modeling and simulation to assess performance and reliability. The study involves the use of genetic algorithms, swarm intelligence, and artificial potential fields for UAV trajectory management. Results: Experimental evaluations conducted in Microsoft Azure and CoppeliaSim EDU environments confirmed the effectiveness of the proposed approaches. Average latency was reduced by 35%, energy consumption was optimized, and uninterrupted data transmission was ensured in 92% of connection failure scenarios. Reliability analysis showed the benefits of component redundancy and predictive failure detection, reducing the probability of critical faults by 22% and shortening recovery time by 42%. Conclusions: Automated resource management in MIS ensures operational stability and continuity for UAV groups even under dynamic operating conditions. Computational optimization and adaptive scaling enhance system performance, reduce transmission delays, and improve energy efficiency. The developed cybersecurity approaches ensure data protection and infrastructure resilience in the face of external threats and network attacks.